Template Dimerization Promotes an Acceptor Invasion-Induced Transfer Mechanism during Human Immunodeficiency Virus Type 1 Minus-Strand Synthesis - Balakrishnan, Mini (American Society for Microbiology, 2003)
The biochemical mechanism of template switching by human immunodeficiency virus type 1 (HIV-1) reverse transcriptase and the role of template dimerization were examined. Homologous donor-acceptor template pairs derived from the HIV-1 untranslated leader region and containing the wild-type and mutant dimerization initiation sequences (DIS) were used to examine the efficiency and distribution of transfers. Inhibiting donor-acceptor interaction was sufficient to reduce transfers in DIS-containing template pairs, indicating that template dimerization, and not the mere presence of the DIS, promotes efficient transfers. Additionally, we show evidence that the overall transfer process spans an extended region of the template and proceeds through a two-step mechanism. Transfer is initiated through an RNase H-facilitated acceptor invasion step, while synthesis continues on the donor template. The invasion then propagates towards the primer terminus by branch migration. Transfer is completed with the translocation of the primer terminus at a site distant from the invasion point. In our system, most invasions initiated before synthesis reached the DIS. However, transfer of the primer terminus predominantly occurred after synthesis through the DIS. The two steps were separated by 60 to 80 nucleotides. Sequence markers revealed the position of primer terminus switch, whereas DNA oligomers designed to block acceptor-cDNA interactions defined sites of invasion. Within the region of homology, certain positions on the template were inherently more favorable for invasion than others. In templates with DIS, the proximity of the acceptor facilitates invasion, thereby enhancing transfer efficiency. Nucleocapsid protein enhanced the overall efficiency of transfers but did not alter the mechanism.